Historical Analysis-A Diagnostic Tool for "Events" Studies: The Impact of the Securities Act of 1933. - Merino, Barbara D.; Koch, Bruce S.; MacRitchie, Kenneth L. (The Accounting Review, 1987)
ABSTRACT: The primary objective of this study is to illustrate why an adequate historical inquiry should be considered an integral part of all "events" studies. We examine a recent events study that attempted to test the impact of the Securities Act of 1933. Our examination of the historical record results in three major criticisms of the author's research design: (1) lack of a control group, (2) an unsubstantiated test period, and (3) apparent misclassification of events (favorable/unfavorable/control) during the test period. We believe that these problems invalidate the conclusion that the Securities Act of 1933 had an adverse impact on stockholders' wealth.